Pengaruh Social Media Marketing Dan Brand Image Terhadap Minat Beli Di Booba Beauty Herbal (Distributor SR12) Depok - Salma Mutiara Zacky; Ivantan Ivantan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of Social Media Marketing and Brand Image on Purchase Intention at Booba Beauty Herbal (SR12 Distributor) Depok, both partially and simultaneously. The research employed a quantitative method with the population consisting of consumers of Booba Beauty Herbal (SR12 Distributor) Depok. The sample consisted of 99 respondents, determined using probability sampling with a simple random sampling technique and calculated using the Slovin formula. Data analysis techniques included descriptive analysis, research instrument testing, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, as well as t-test and F-test using SPSS software.The results indicate that Social Media Marketing has a positive and significant partial effect on Purchase Intention, with the regression equation Y = 11.497 + 0.712X₁, a correlation coefficient of 0.715, and a coefficient of determination of 51.1%. Brand Image also has a positive and significant partial effect on Purchase Intention, with the regression equation Y = 7.373 + 0.820X₂, a correlation coefficient of 0.876, and a coefficient of determination of 76.8%. Simultaneously, Social Media Marketing and Brand Image have a positive and significant effect on Purchase Intention, as indicated by the regression equation Y = 3.955 + 0.217X₁ + 0.681X₂, a correlation coefficient of 0.891, and a coefficient of determination of 79.3%, while the remaining 20.7% is influenced by other variables not examined in this study.